Вдосконалення системи прийому масової сировини в логістичній системі металургійного підприємства - Хара, Марина; Врадій, Віталій; Сарахман, Артем (ТзОВ «Галицька видавнича спілка», 2021)
The issues of improving the system for receiving bulk raw materials in the logistics system of a metallurgical enterprise in winter conditions are considered.
Improving the system for receiving bulk raw materials in the logistics system of a metallurgical enterprise
Keywords: 658.788.5; 669.013